Koncept „gołąb” w językowym obrazie świata Ukraińców, Rosjan i Polaków - Kowalewska, Olena (Studia Ukrainica Posnaniensia, 2024)
The article is dedicated to analysing the linguistic aspect of the concept “dove” in how Russian, Ukrainian and Polish languages depict the world. The aim of the article is to identify ver-balizers of the concept, as well as similarities and dissimilarities in the various semantic meanings shaping the structure of the concept in these three different but also related worldviews. There are different ethnocultural, mythologic and symbolic meanings connected with the conceptual meaning of the dove. The linguistic cultures in question share a common polysemanticity of this concept, which reflects both the positive and negative connotations (of which the former are much more common). The semantic structure is dominated by dove images in Christian and Slavic culture (common to the three worldviews), as well as peripheral ones, which are linked with mythology, tradition and folk beliefs (distinct and individual for the linguistic cultures studied here).